2007
DOI: 10.1007/s00335-007-9015-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of chromosomal inversion of the mouse hairy ears (Eh) mutation associated with cleft palate

Abstract: The hairy ears (Eh) mutation in the mouse originated from neutron irradiation experiments and is associated with chromosomal inversion on chromosome 15. Eh/+ mice have small pinna and extra hairs on the pinna but the phenotypic features of Eh/Eh mice are unclear. In this study we found that Eh/Eh mice died shortly after birth and had a cleft palate caused by impaired growth of palate shelves. Because genes located on the breakpoints of inversion are likely to be responsible for the defects associated with chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The products of the third nested PCR were cloned into pGEM‐T Easy vector (Promega, Madison, WI, USA) and sequenced using an ABI Prism 310 Genetic Analyzer and BigDye terminator v3.1 (Applied Biosystems, Foster City, CA, USA). For 3’‐RACE analysis, cDNA was synthesized using a 3'RACE oligo‐dT primer (Katayama et al 2007). The first PCR was performed with a 3'RACE adaptor and Wwox‐3 F, and the second PCR with a 3'RACE adaptor and 3'RACE TSP 1.…”
Section: Methodsmentioning
confidence: 99%
“…The products of the third nested PCR were cloned into pGEM‐T Easy vector (Promega, Madison, WI, USA) and sequenced using an ABI Prism 310 Genetic Analyzer and BigDye terminator v3.1 (Applied Biosystems, Foster City, CA, USA). For 3’‐RACE analysis, cDNA was synthesized using a 3'RACE oligo‐dT primer (Katayama et al 2007). The first PCR was performed with a 3'RACE adaptor and Wwox‐3 F, and the second PCR with a 3'RACE adaptor and 3'RACE TSP 1.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Hoxc5 positive cells were noticeably increased at E14.5 ( P < 0.001) in Eh / Eh mice. Previously it has been demonstrated that strong expression of the Hoxc5 gene is detected in the palates of Eh / Eh mice, while no Hoxc5 expression is detected in +/+ mice at this stage, suggesting that the elevated expression of Hoxc5 is likely to be responsible for the cleft palate in Eh / Eh mice (Katayama et al ). Our data showed that the distribution of Hoxc5 tend to localize in epithelial cells during palate formation in the palatal shelves of +/+.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, the palatal shelves do not elevate in the Hoxa2 knockout mouse, suggesting that the absence of Hoxa2 induces an increase in mesenchymal cell proliferation, which alters the palate growth pattern and affects palatal elevation (Smith et al ). However, in Eh / Eh mice, no significant differences in cellular proliferation or apoptosis (Katayama et al ) in the palatal shelves were observed; therefore, the cleft in Eh / Eh is not likely due to decreased cell proliferation or increased cell death (Katayama et al ). In this study, no difference was observed in the PCNA‐positive cells; moreover, it appeared that PCNA distribution patterns were similar to those of Hoxc5, though it remains unclear whether Hoxc5 could be involved in proliferation and differentiation of the cells of the palatal shelves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations